Utilitarianism : A Very Short Introduction - Lazari-Radek, Katarzyna de; Singer, Peter, 1946- (Great Claredon Street Oxford University Press, 2017)
In this Very Short Introduction Peter Singer and Katarzyna de Lazari-Radek provide an authoritative account of the nature of utilitarianism, from its nineteenth-century origins, to its justification and its varieties. Considering how utilitarians can respond to objections that are often regarded as devastating, they explore the utilitarian answer to the question of whether torture can ever be justified. They also discuss what it is that utilitarians should seek to maximize, paying special attention to the classical utilitarian view that only pleasure or happiness is of intrinsic value. Singer and de Lazari-Radek conclude by analysing the continuing importance of utilitarianism in the world, indicating how it is a force for new thinking on contemporary moral challenges like global poverty, the treatment of animals, climate change, reducing the risk of human extinction, end-of-life decisions for terminally-ill patients, and the shift towards assessing the success of government policies in terms of their impact on happiness.
Include Illustrations and Index
Keywords: a